Tradisi Marsialapari (Gotong Royong) Petani Suku Mandailing di Pintu Langit Jae Kota Padangsidimpua - Harahap, Hotmarina Sari; Dora, Nur Iza (JURNAL EDUKASI NONFORMAL, 2023)
In Pintu Langit Jae Village, Padangsidimpuan District, this study attempts to characterize the Marsialapari-based local knowledge education that Mandailing tribal farmers possess when working on agricultural land, such as rice fields, snake fruit plantations, and rubber. The purpose of this study is to ascertain the significance and worth of local wisdom education, or Marsialapari, for farmers in Pintu Langit Jae Village, Padangsidimpuan District. With an anthropological approach, this research employs a descriptive qualitative methodology. Participatory observation, documentation, and in-depth interviews with informants were used to collect data. Subsequently, conduct ethnographic interviews, write ethnographies, and make notes in order to apply data analytic methodologies. The study's findings demonstrate the importance of teaching farmers in Pintu Langit Jae Village, Padangsidimpuan District, based on the native Marsialapari knowledge. This education emphasizes the values of unity, fraternity, togetherness, and mutual aid for rural communities. The Batak Mandailing and Toba ethnic groups make up the population of Pintu Langit Jae Village. For farmers, preserving peace and fraternity among communities is of great importance and significance, as per the indigenous knowledge of Marsialapari.